Associations between sexual identity and caries risk indicators among adolescents and adults in Nigeria: implications for policy and actions - Folayan, Morenike Oluwatoyin; Oginni, Olakunle; Ibigbami, Olanrewaju; Adeniyi, Abiola; Lusher, Joanne (Frontiers in Oral Health, 2025)
BackgroundThere is little known about the oral health profile of sexual minority individuals in Africa. The study aimed to investigate the association between sexual identity and dental caries risk behaviors of adolescents and adults in Nigeria.MethodsThis was a secondary analysis of data collected from participants aged 13 years and above recruited using an online electronic survey between 16th September and 31st October 2020. The dependent variable was dental caries risk behaviour (daily tooth brushing twice a day or more, daily consumption of refined carbohydrates in-between-meals thrice a day or more, history of dental service utilisation, and poor knowledge of dental caries prevention). The independent variable was sexual identity (heterosexual and sexual minority individuals). Four multivariate regression models were developed to assess the associations between sexual identity and each of the dependent variables. Each model was adjusted for age, sex, educational level, employment status, and marital status.ResultsThe data of 2,772 respondents were extracted for analysis. Sexual minority individuals had significantly lower odds of consuming refined carbohydrates in-between-meals three times daily or more (AOR: 0.53; 95% CI: 0.43–0.64; p < 0.001), tooth brushing twice daily or more (AOR: 0.82; 95% CI: 0.68–0.99; p = 0.037), and making use of a dental service within the last year before the survey (AOR: 0.66; 95% CI: 0.55–0.79; p < 0.001).ConclusionWhile sexual minority individuals in Nigeria exhibit some protective behaviors (lower sugar intake), their reduced dental care utilization and brushing frequency signal a need for inclusive, equity-focused oral health policies. Further research is needed to provide evidence for the development of a comprehensive oral healthcare programme that addresses the needs of the sexual minority population.